Workbook/Study Guide to accompany Managerial Accounting - C.Brewer Peter (McGraw-Hill, 2004)
This study aid provides suggestions for studying chapter material, summarizes essential points in each chapter, and tests students’ knowledge using self-test questions and exercises. --This text refers to an out of print or unavailable edition of this title.